Resilient Data Protection in Fog-Cloud Environments Using Fragmentation and Advanced Cryptography - Tagore, Yuvana; Reddy, R.Vijaya Kumar; Vengatesh, T. (Journal of Neonatal Surgery, 2025)
Unless users use a cloud storage service for their sensitive data, the storage service is excellent. Once data is outsourced to the cloud, the cloud server has complete access to and control over the user's data. It can have the capacity to read and search user data. Emerging cyber threats to cloud storage include data loss, malicious modification, and privacy invasion. Fog server-based three-layer architecture for safe storage has just been introduced. According to the design, some data will be saved on the user's local system, in the cloud, and fog. A fraction of the data in the cloud and their unique hash method require additional processing and storage. An approach to cloud storage based on fog is used in this study. In that technique, data is divided into many blocks using the XOR operator, and these multiple blocks are then combined into two or three blocks. As a result, we increase the security of the fog server for a resilient fog-centric cloud computing architecture and we improve the cryptosystem to secure data without revealing any information from it using this technique. Data is protected from unauthorised access, modification, and deletion via the fog-centrioud storage system.